Medical Oncology Group of Australia position statement: COVID‐19 vaccination in patients with solid tumours. Issue 6 (21st June 2021) - Kanjanapan, Yada; Blinman, Prunella; Underhill, Craig; Karikios, Deme; Segelov, Eva; Yip, Desmond
Abstract: People with cancer are vulnerable to increased morbidity and mortality from the coronavirus disease 2019 (COVID‐19). COVID‐19 vaccination is key to protecting the population of people with cancer from adverse outcomes of SARS‐CoV‐2 infection. The Medical Oncology Group of Australia aimed to address the considerations around COVID‐19 vaccination in people with cancer, in particular, safety and efficacy of vaccination. The assessment of patients with generalised allergic reaction to anti‐cancer therapy containing vaccine components and practical implementation of vaccination of people on active anti‐cancer therapy are also discussed.